Density Relationship of the Assassin Bugs Sycanus falleni Stål and Sycanus croceovittatus Dohrn (Hemiptera: Reduviidae) and Principal Corn Pests (Noctuidae: Lepidoptera) in Hoa Binh Province, Vietnam - Lam, Truong Xuan; Lien, Nguyen Thị Phuong; Cuong, Nguyen Quang; Ngat, Tran Thị (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The group of assassin bugs including the Sycanus falleni and Sycanus croceovittatus species were such potential candidates for biocontrol of key pests (fall armyworm Spodoptera frugiperda, black cutworm Agrotis ypsilon, cotton bollworm Heliothis armigera Hübner, maize caterpillar Mythimna loreyi (Lepidoptera: Noctuidae)) on Corn biomass in Hoa Binh Province. Seven species of assassin bugs belonging to the family Reduviidae as S. falleni Stål, S. croceovittatus Dohrn, Coranus spiniscutis Reuter, Coranus fuscipennis Reuter, Polytoxus fuscovittatus (Stål), Endochus nigricornis Stål, Sphedanoletes pubinotum Reuter were recorded on the Corn biomass, of which S. falleni and S. croceovittatus were common. The relationship between the density of the group of assassin bugs and the density species S. falleni, S. croceovittatus had a close relationship with each other (R=0.81, R=0.72 respectively). The relationship between the density of the group of assassin bugs and the density of their prey (4 key pests) on the Corn biomass in the Winter crops and Summer-fall crops were a close relationship with each other (R2= 0.5166, R2= 0.7274 respectively). The relationship between the density of the species S. falleni, S. croceovittatus and the density of their prey (4 key pests) in the Winter crops, and the Summer fall crops were a close relationship with each other (R2 =0.7815, R2 =0.5396 respectively). However, these relationships were not closely related in the Spring-Summer crops and Winter-Spring crops.